1994
DOI: 10.1364/ao.33.002921
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric tomography for flow visualization of density fields in supersonic jets and convective flow

Abstract: Tomographic methods are used for the investigation of three-dimensional compressible flow fields by means of interferometric methods. A modified algebraic reconstruction technique algorithm is applied. The algorithm proved to give reliable reconstructions from experimentally measured projection data in the case of an unrestricted angular view. The method was used for the reconstruction of density distributions of weakly perturbed supersonic free jets exiting from a deformed Laval nozzle. Even small perturbatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…In general, multiple measurements of the flow along different axes are combined, and the 3D density map is extracted using mathematical procedures such as filtered backprojection [27] or algebraic reconstruction techniques (ART) [28]. Often, some modifications of general ART are used, such as averaging ART (AVART) [29] or simultaneous iterative reconstruction technique (SIRT) [30,31]. Tomographic measurements are also needed for superposed or colliding flows, or when the initially symmetric gas flow is perturbed by inserting wires [32] or other obstacles [33], or by machining with a high-intensity laser pulse [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…In general, multiple measurements of the flow along different axes are combined, and the 3D density map is extracted using mathematical procedures such as filtered backprojection [27] or algebraic reconstruction techniques (ART) [28]. Often, some modifications of general ART are used, such as averaging ART (AVART) [29] or simultaneous iterative reconstruction technique (SIRT) [30,31]. Tomographic measurements are also needed for superposed or colliding flows, or when the initially symmetric gas flow is perturbed by inserting wires [32] or other obstacles [33], or by machining with a high-intensity laser pulse [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, this technique has been mainly used in the structural visualization for low temperature [1,2], low and high speed complex flow fields [3][4][5], the density measurement [6], as well as the temperature measurement for the flow fields whose temperature is not too high [7]. Until now, it is rarely reported that this technology could be used in the structural visualization, or the temperature and the electron number density measurement for the high-temperature complex flow fields [8].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, OCT has played important roles in visualizing various flow [1] and hot flow fields [2,3], as well as being applied in measuring key parameters for various flow fields [1,[4][5][6][7]. In view of these advantages and applications of OCT, the feasibility of it on measuring flow velocity distribution of gas jet flow field is worthy to be analyzed.…”
Section: Introductionmentioning
confidence: 99%